If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -1) = x + -16 Reorder the terms: 3(-1 + x) = x + -16 (-1 * 3 + x * 3) = x + -16 (-3 + 3x) = x + -16 Reorder the terms: -3 + 3x = -16 + x Solving -3 + 3x = -16 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + 3x + -1x = -16 + x + -1x Combine like terms: 3x + -1x = 2x -3 + 2x = -16 + x + -1x Combine like terms: x + -1x = 0 -3 + 2x = -16 + 0 -3 + 2x = -16 Add '3' to each side of the equation. -3 + 3 + 2x = -16 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = -16 + 3 2x = -16 + 3 Combine like terms: -16 + 3 = -13 2x = -13 Divide each side by '2'. x = -6.5 Simplifying x = -6.5
| 2(x-15)=8 | | 5x-11+2x+25= | | 2x^4(21+8x+2x^4)=0 | | 16t^2+48t+160= | | (2w-9)w=110 | | 2x^3-96x-256=0 | | -2(w-7)=w-1 | | 12h-3h^2+h-4=0 | | 1.6=x/700 | | 4^1/2 | | 4(x-6)+15=13 | | 6b-(b/2) | | 7x-2y=26 | | 3x^2-40=95 | | y=158x+116 | | x/4.90=2.40-x/336 | | 9x-15=3(x+9) | | 2t^2+t+6= | | (8x+3)(3x^2-14x-5)= | | .33(5x-8)=7 | | 19=4(w-2)-7w | | .33(5x)+8=-7 | | A=3600(1+.11(2)) | | 3/4n-9=-12 | | x^4-45x^2-196=0 | | r=0.814 | | 0.3=x/100 | | -7/10 | | 3+4*x=x+30 | | x-12+x-44+x-44+x+x=360 | | (9-6i)(4+i)= | | 4(2x+13)-3(x-4)=2 |